Active vibration control of truncated conical shell under harmonic excitation using piezoelectric actuator. (June 2020) - Morteza Fatemi Moghaddam, Seyyed; Ahmadi, Habib
Abstract: In this study, active vibration control of an FGM truncated conical shell, subjected to the harmonic excitation, is investigated via a semi-analytical method. The governing equations of truncated conical shells in conjunction with piezoelectric layers are derived using Donnell shell theory and von Karman's non-linearity. Then, the dynamic equation of the system is discretized using Galerkin method to obtain the ordinary differential equation of system. Using the semi-analytical method by means of perturbation theory, the frequency response of superharmonic and sub-harmonic analysis of the system is performed. Then, using the piezoelectric smart materials, the active vibration control for the truncated conical shell is investigated and frequency-amplitude functions are analyzed for the superharmonic and subharmonic resonances. The results presents the influence of excitation amplitude and cone vertex angle on the frequency-amplitude response and in specific the effect of different control gain coefficients on the system's vibration behavior. Finally, the performance of active control strategy is investigated by means of the time response of system equipped with piezoelectric layers for different types of the FG distribution in thickness direction. Highlights: The vibrations of functionally graded truncated conical thin shell are investigated under harmonic lateral excitation. The truncated conical shell is a functionally graded cone with piezoelectric layer as sensor and actuator. Using the perturbation theory, the resonances behavior of the system including of piezoelectric layers are analyzed. Influences of the piezoelectric layers and cone shell geometry on the system behavior are investigated. Influence of the controller coefficients on the nonlinear resonances behavior of the system is investigated.